(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The spreading of Aonidiella aurantii (Maskell) during the last ten years throughout the ltalian citrus-groves led to carry out studies on its mortality key factors. The latter ones were detected by means of multiple linear regression analysis. Field investigations were carried out in two citrus orchards with different infestation levels, cultivars and mesoclimatic conditions. Low temperatures have been more effective than the higher ones in containing the insect populations, while relative humidity had no influence. Among natural enemies, Aphytis melinus DeBach and Chilocorus bipustulatus (L.) have been the most effective. Particularly the ectoparasitoid A. melinus resulted the most important regulating factor of A. aurantii population at any host density levels. On the contrary, the predator C. bipustulatus has been effective only at the high prey population level, causing, in that case, the rapid decline of the scale population.